2018
DOI: 10.3892/ijmm.2018.3649
|View full text |Cite
|
Sign up to set email alerts
|

Physcion 8‑O‑β‑glucopyranoside extracted from Polygonum�cuspidatum exhibits anti‑proliferative and anti‑inflammatory effects on MH7A rheumatoid arthritis‑derived fibroblast‑like synoviocytes through the TGF‑β/MAPK pathway

Abstract: The present study aimed to investigate the anti-arthritic effect of physcion 8-O-β-glucopyranoside (POGD) and its possible mechanisms. The anti-proliferative effects of POGD on MH7A cells were detected using a CCK-8 assay, and the release of pro-inflammatory cytokines, interleukin (IL)-1β, IL-6, IL-8, IL-12 and IL-17A, were determined by ELISA. A type II collagen-induced arthritis (CIA) rat model was established to evaluate the anti-arthritic effect of POGD in vivo. The paw volumes, arthritis indices and serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…It is effective against various cancers, including breast cancer [6], glioblastoma [7], hepatocellular carcinoma [8], oral squamous cell carcinoma [9], and osteosarcoma [10]. Moreover, PG extracted from Polygonum cuspidatum is shown to exert anti-proliferative and anti-inflammatory impacts on MH7A rheumatoid arthritis-derived fibroblast-like synoviocytes [11]. However, it is largely unknown whether PG exerts a protective effect on DR, let alone the underlying mechanism involved.…”
Section: Introductionmentioning
confidence: 99%
“…It is effective against various cancers, including breast cancer [6], glioblastoma [7], hepatocellular carcinoma [8], oral squamous cell carcinoma [9], and osteosarcoma [10]. Moreover, PG extracted from Polygonum cuspidatum is shown to exert anti-proliferative and anti-inflammatory impacts on MH7A rheumatoid arthritis-derived fibroblast-like synoviocytes [11]. However, it is largely unknown whether PG exerts a protective effect on DR, let alone the underlying mechanism involved.…”
Section: Introductionmentioning
confidence: 99%
“…The two structurally related anthraquinones (chrysophanol and physcion) showed similar behavior in vitro and in silico. On contrary to curcumin, both compounds showed their ability to bind effectively to all of the MAPKs enzymes but with lower extent in case of ERK1/2, which can be explained in the light of the previously mentioned criteria, and is in agreement with former reports indicating the ability of physcion glycoside to exhibit anti-inflammatory effect against rheumatoid arthritis derived fibroblast-like synoviocyte cell line by inhibiting phosphorylation of p38, JNK and ERK MAP kinase [48,49,50]. Yet, there were no studies addressing the ability of anthraquinones to inhibit MK-3.…”
Section: Resultssupporting
confidence: 88%
“…Modern pharmacological studies have indicated that extracts from P. cuspidatum have anti-inflammatory, antioxidant, and hepatoprotective properties and could be to treat cancer and other diseases (Zhang et al, 2013; Olaru et al, 2015; Sohn et al, 2015; Abu-Amero et al, 2016; Liu and Huang, 2016; Geng et al, 2018). Extensive photochemistry investigations have led to the isolation and identification of more than 67 compounds from the roots and leaves of P. cuspidatum , providing chemical evidence for its pharmacological effect (Vastano et al, 2000; Yi et al, 2007; Shan et al, 2008).…”
Section: Introductionmentioning
confidence: 99%